2013
DOI: 10.1002/ijc.28560
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori antibody responses and evolution of precancerous gastric lesions in a Chinese population

Abstract: Helicobacter pylori-specific proteins are involved in gastric carcinogenesis. To investigate the seroprevalence of six H. pylorispecific antibodies in patients with different gastric histology, and the impact of seropositivities on the evolution of precancerous gastric lesions, a follow-up study was conducted in Linqu County, China. The seropositivities for CagA, VacA, GroEL, UreA, HcpC and gGT were assessed by recomLine analysis in 573 H. pylori-positive subjects and correlated with evolution of precancerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
10
29
0
1
Order By: Relevance
“…In this context, Helicobacter pylori infection, smoking, and age have positive associations, whereas nonsteroidal anti-inflammatory drugs (NSAIDs), low salt intake, and a high-fiber diet have an inverse association with gastric cancer (Mohebbi et al, 2008;Yavari et al, 2008;Malekzadeh et al, 2009;Pan et al, 2014). In addition to environmental factors, genetic factors may contribute to this phenomenon by alteration of cellular activities such as DNA repair, inflammatory response, tumor suppression, and carcinogen metabolism (Bonequi et al, 2013;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In this context, Helicobacter pylori infection, smoking, and age have positive associations, whereas nonsteroidal anti-inflammatory drugs (NSAIDs), low salt intake, and a high-fiber diet have an inverse association with gastric cancer (Mohebbi et al, 2008;Yavari et al, 2008;Malekzadeh et al, 2009;Pan et al, 2014). In addition to environmental factors, genetic factors may contribute to this phenomenon by alteration of cellular activities such as DNA repair, inflammatory response, tumor suppression, and carcinogen metabolism (Bonequi et al, 2013;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…According to our previous results from the same intervention trial, the subjects with increasing number of H. pylori seropositive antibodies at baseline showed a higher risk for progression to gastric cancer (42). Both of these prospective studies suggested a potential preferential population for anti- H. pylori treatment in the subjects with multiple seropositive antibodies, especially FliD and HapA, for their higher risk of gastric cancer and easier eradication tendency.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Pan et al examined the relationship between seropositivity for CagA, VacA, GroEL, urease subunit A (UreA), γ-glutamyl transpeptidase (gGT) and HcpC and the development of gastric lesions during the follow-up period in patients with a risk for precancerous gastric lesions at baseline [47]. The presence of antibodies for each specific antigen was examined by using the recomLine H. pylori test system, which is a line immune assay.…”
Section: Cytotoxin-associated Gene a Antibodiesmentioning
confidence: 99%